Analisis Kinerja Motor Bakar Berbahan Bakar Campuran Pertalite Dan Bioetanol Dari Sampah Organik - Mukhtar, Muharnif; A, Arfis; Febrian, Muhammad Kevin; Refan, Mahammad (Fakultas Teknik UMSU, 2024)
The increasing availability of fossil fuels and high emissions from combustion which have an impact on global warming has continued to emerge in recent years. One solution to this problem is the use of alternative fuel sourced from organic waste to become bioethanol fuel. The use of bioethanol as a fuel mixed with pertalite is expected to reduce consumption and dependence on fossil fuels. This research aims to analyze the effect of a mixture of biethanol and pertalite on the performance of a 150 cc 4 stroke of SI Engine. The test method was carried out by analyzing torque, power and specific fuel consumption using a mixture of pertalite and bioethanol 10% (PB10), 20% (PB20) and 30% (PB3) as well as 100% pertalite wiith a rotation variations of 5000 – 9000 rpm. The results of research performance show that there is an increase in torque and power with the addition of bioethanol into pertalite. Specific fuel consumption will decrease as the percentage of bioethanol mixed with pertalite fuel increases